Understanding Concept Profile Distance Line to Line on space of Geometry High School Students Level IQ Normal in terms of Gender differences - Suprianto Suprianto (Proceedings of The ICECRS, 2017)
Geometry in particular the concept of distance is part of the metamatic science that is widely applied in the real world. The purpose of this research is to know the profile of distance understanding especially students high school student with normal IQ level in terms of gender difference. The research method used is explorative qualitative method, where the researcher as the main subject in the research. To describe the concept of distance, a study of four aspects, namely: 1) understanding aspect, 2) representation aspect, 3) non sample aspect, 4) application aspect to calculate distance. The results obtained from the study, female students in terms of understanding the concept of distance from line to line better than male students, while for the other three aspects, there is no significant difference between male students and female students. The results of this study differ from the results of previous research, which states that male students are better than female students in understanding the mathematical concepts. This result can give implication about opinion and treatment learning process for matemathics theacer’s, that nothing diferences for capacity mathematics as specially about distance concept line to line between male and female students.